Philippine Merchant Marine Academy (PMMA) Shipboard Monitoring System - Dr. Froilan D. Mobo; Friedr (International Journal of Human Computing Studies, 2020)
The main purpose of this study is to customize a Shipboard Monitoring for Philippine Merchant Marine Academy. It also shows an excellent reliability with respect to transmission ratio speed of sensor nodes and a significant connectivity between nodes located in different compartments and decks separated by metallic watertight doors using the shipboard monitoring system, (Kdouh et al., 2013).